The intramolecular Diels–Alder vinylfuran (IMDAV) reaction: a short approach to aza-analogues of pinguisane-type sesquiterpenes. Issue 30 (22nd July 2015) - Horak, Yuriy I.; Lytvyn, Roman Z.; Homza, Yuriy V.; Zaytsev, Vladimir P.; Mertsalov, Dmitriy F.; Babkina, Maria N.; Nikitina, Eugenia V.; Lis, Tadeusz; Kinzhybalo, Vasyl; Matiychuk, Vasyl S.; Zubkov, Fedor I.; Varlamov, Alexey V.; et al.
Graphical abstract: Abstract: The reaction of readily accessible (3-furyl)allylamines with maleic anhydride, followed by a domino sequence involving acylation/cycloaddition/proton shift steps, led to the formation of furo[2, 3- f ]isoindoles—the aza-analogs of pinguisane-type sesquiterpenes. The key intramolecular Diels–Alder vinylfuran (IMDAV) reaction proceeded under mild conditions, with high levels of diastereoselectivity and satisfactory yields.